2015
DOI: 10.1016/j.hrthm.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

J-wave syndromes: Brugada and early repolarization syndromes

Abstract: A prominent J wave is encountered in a number of life-threatening cardiac arrhythmia syndromes, including the Brugada (BrS) and early repolarization (ERS) syndromes. BrS and ERS differ with respect to the magnitude and lead location of abnormal J waves and are thought to represent a continuous spectrum of phenotypic expression termed J wave syndromes. Despite two decades of intensive research, risk stratification and the approach to therapy of these two inherited cardiac arrhythmia syndromes are still undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 195 publications
(168 reference statements)
2
126
1
7
Order By: Relevance
“…In this study, we investigated whether a J-wave could The intraventricular conduction delay in HCM is also known to initiate notching of the QRS complex (fragmented QRS complex) (21). We and others (22,23) reported that the presence of fragmented QRS complexes, defined as the presence of an additional R-wave (R 0 ), notching in the nadir of the S-wave, or the presence of >1 R 0 on the 12-lead ECG, was associated with either heart failure with hospitalization or arrhythmic events in patients with HCM.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated whether a J-wave could The intraventricular conduction delay in HCM is also known to initiate notching of the QRS complex (fragmented QRS complex) (21). We and others (22,23) reported that the presence of fragmented QRS complexes, defined as the presence of an additional R-wave (R 0 ), notching in the nadir of the S-wave, or the presence of >1 R 0 on the 12-lead ECG, was associated with either heart failure with hospitalization or arrhythmic events in patients with HCM.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be the result of the location of the right ventricular outflow tract in the chest [31,32] and its role in the pathophysiology of BrS [33]. Some data suggest that the prognosis of BrS patients remains the same irrespective of the intercostal space used for diagnosis [31].…”
Section: Elevated Right Precordial Leadsmentioning
confidence: 99%
“…A long list of genes have been associated with BrS (Table 2), the most common of which is SCN5A, which can be found in up to 28% of patients [33]. Rare variants in SCN10A and in genes affecting the calcium current can also be found in a significant minority of patients.…”
Section: Genetic Testingmentioning
confidence: 99%
“…Az entitás EKGosztályozási szempontból az úgyne vezett Jhullámszindrómák csoportjába tartozik a korai repolarizációval együtt [7]. Patognomikus az 1es típusú BrugadaEKGmintázat, amelynek lényege egy ≥2 mm es deszcendáló, "vitorlaszerű" [8], "coved" STeleváció, amely legalább egy jobb oldali mellkasi elvezetésben je len van [9].…”
Section: A Rare Ecg Manifestation Of Left Sided Pneumothorax: Inferiounclassified
“…A BrSzt szá mos gén mutációja okozhatja, amelyek következménye a befelé irányuló depolarizáló áramok (I Na és I Ca ) erősségé nek csökkenése, illetve a kifelé irányuló, repolarizáló ára mok (például I to , I KATP ) intenzitásának fokozódása [5]. Az EKGelváltozás és a malignus kamrai aritmiák elsődle ges elektrofiziológiai alapja a repolarizáció transmuralis inhomogenitása, amely 2es fázis típusú reentryt indít be, következményes kamrai ectopiával, illetve polimorf kam rai tachycardiával és kamrafibrillációval [6].Az entitás EKGosztályozási szempontból az úgyne vezett Jhullámszindrómák csoportjába tartozik a korai repolarizációval együtt [7]. Patognomikus az 1es típusú BrugadaEKGmintázat, amelynek lényege egy ≥2 mm es deszcendáló, "vitorlaszerű" [8], "coved" STeleváció, amely legalább egy jobb oldali mellkasi elvezetésben je len van [9].…”
unclassified